Training non-native speech sounds results in long-lasting plastic changes – Hard-wiring new memory traces takes time - Tamminen, Henna (Elsevier BV, 2025)
Training of a foreign language speech sound pair may lead to the formation of new memory traces in young adults who are not very experienced in the target language, as well as to the strengthening of existing memory traces in advanced target language students. We used listen-and-repeat training to test whether previously formed memory traces exist approximately a year later. Further, we compared these learning results with those obtained from advanced target language students. Both groups participated in a recording that was identical to the one that the less experienced learners had already completed a year before, but only once and without training. The experiments included EEG recordings measuring mismatch negativity (MMN) and N1, as well as listening tests. The less experienced learners’ MMN responses were similar to those of advanced students, and their N1 amplitude had increased close to that of the advanced students. These results suggest long-lasting speech memory traces resulting from a brief training and the development of increased sensitivity.